TINJAUAN AKTA PERDAMAIAN YANG DIBUAT NOTARIS SEBAGAI UPAYA PENYELESAIAN SENGKETA PERDATA - , AHMAD ANTA SETIAWAN ([Yogyakarta] : Universitas Gadjah Mada, 2013)
This thesis writing is aimed to study the Notaryâs deed of peace as effort on the completion of civil dispute. By viewing on the implementation of Notary position concretely through practices and related with provision from the regulation legislation. This research is juridical empirical research, which prioritizing an approach on issues by studying the phenomena on ecountered problems in this research and associated with the regulation legislation. The field research conducted by interviews using media in form of interview guidance. Then the primary data and secondary data will be analyzed qualitatively by structuring them systematically and based on inductive method then drawn in a conclution from each of issues formulation. Result of this research showed First, implementation of Article 15 UUJN in relating to the making of deed of peace, to wit, explaining, that Notary profession is an official being appointed by the government to receive authority attributively from the state to serve the communityâs necessity so the legal relationship between those who concerned is occurred, which then the authentic deed is used as legal evidence, and has perfect proof strength. Then pursuant to Article 15 Number (2) Letter E, that the Notary could involved and participated as legal counselor for the parties who involved within those deed of peace, by providing legal advices which certainly included limitations, to achieve this deed of peace in order to prevent the dispute. Second, whether or not a deed of peace that made in front of the Notary accommodates the partiesâs interest who being dispute, is very depend on good faith of each parties that agreed to resolve the dispute through Notary deed of peace. Without any good faith and voluntary attitude to implement and subjecting themselves upon the agreement which has been stated in the peace agreement, it is impossible the implementation of the peace agreementâs content is embodied.